2006
DOI: 10.1196/annals.1365.022
|View full text |Cite|
|
Sign up to set email alerts
|

Fertility Drugs and Gynecologic Cancer

Abstract: Fertility drugs (FD) are spreading worldwide fast and therefore many studies have reviewed the possible association between the use of these drugs and cancer. Since the drugs used for ovulation induction during in vitro fertilization (IVF) like hCG, hMG, rFSH increase the levels of gonadal hormones, concerns have grown regarding the risk of developing cancer in breast, ovary, endometrium, and other target organs. In this review, we discuss a number of different studies published in recent years that show no as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
1
5
0
2
Order By: Relevance
“…76 Subsequent studies have been mainly reassuring although suggesting that the type and duration of treatment may increase the malignancy risk. 77 An increased risk for endometrial cancer in patients undergoing infertility treatment has been reported. 75 Breast cancer is widely recognized as having a hormonal etiology; therefore, a possible role of fertility medications to promote breast cancer has been hypothesized, although large studies did not find an associated risk for breast cancer.…”
Section: Art Treatment and Cancer Riskmentioning
confidence: 99%
“…76 Subsequent studies have been mainly reassuring although suggesting that the type and duration of treatment may increase the malignancy risk. 77 An increased risk for endometrial cancer in patients undergoing infertility treatment has been reported. 75 Breast cancer is widely recognized as having a hormonal etiology; therefore, a possible role of fertility medications to promote breast cancer has been hypothesized, although large studies did not find an associated risk for breast cancer.…”
Section: Art Treatment and Cancer Riskmentioning
confidence: 99%
“…Although egg donation appears to be a relatively safe procedure, women do face some physical and psychological risks in donating oocytes, undergoing ovarian hyperstimulation and egg retrieval, and are inconvenienced by weeks of required therapy. Concerns remain as to whether exposures to gonadotrophins increase the incidence of ovarian neoplasms and cancers (Mertes and Pennings, 2007), although well designed retrospective studies have failed to document a relationship (Brinton et al ., 2005; Kanakas and Mantzavinos, 2006). Thus, payment may well be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions of reports on associations between fertility medication use and other cancers (melanoma, colon cancer, and hematological cancers) are limited by the very small number of cases, but are overall reassuring with some reports detecting an increased risk in certain subgroups only [30,31,[46][47][48][49].…”
Section: Fertility Medications and Cancers Of Nonreproductive Organsmentioning
confidence: 91%
“…The study by Kotsopoulus [39] Venn et al (1995) Cohort of infertile women 1978-1992; (median F/U: 5.2 years in exposed and 7.6 years in unexposed groups) 5564 exposed to fertility medication 4794 not exposed to fertility medications and general population Breast cancer exposed vs general population SIR: 0.89; 95% CI: 0.55-1. 46 Breast cancer not exposed vs general population SIR: 0.98; 95% CI: 0.62-1.56 Breast cancer exposed vs not exposed: RR: 1.11; 95% CI: 0.56-2.20 [26] Venn et al (1999) Cohort of infertile women 20,583 exposed to fertility drugs 9083 not exposed to fertility drugs and general population Review et al evaluated the risk of breast cancer among women with an increased inherited risk who had undergone fertility treatment. Fertility medication use did not further increase the risk of these patients (OR: 1.21; 95% CI: 0.81-1.82) [42].…”
Section: Fertility Medications and Breast Cancermentioning
confidence: 97%